Gender and the Canadian Armed Forces: Does Change Mean Feminist Progress? - Eichler, Maya (Atlantis)

(untitled) (Mount Saint Vincent University, 2020)
An introduction to the special issue Gender and the Canadian Armed Forces: Does Change Mean Feminist Progress? It situates the special issue within the significant gendered changes that have occurred within the Canadian Armed Forces over the past two decades. The introduction highlights the importance of continued feminist critique of, and engagement with, the military to achieve feminist progress.